Level of User’s Satisfaction Towards Indoor Air Quality at Indoor Sports Hall - Hishamuddin, Danial Fikri; Rahmat, Muhamad Hanafi; Abu Bakar, Hasniza (Recent Trends in Civil Engineering and Built Environment, 2021)
Basically, Indoor Air Quality (IAQ) refers to the level of air quality inside the building. People nowadays prefer to do indoor exercises rather than doing outdoor activities as they can exercise anytime without concerning the weather. However, poor indoor air quality can give impact on athletes and their performances. Temperature (℃), relative humidity (RH), carbon dioxide (), total volatile organic compound (TVOC), formaldehyde (HCHO), respirable suspended particulates (RSP), ozone (O3), airborne bacterial count (ABC) and carbon monoxide (CO) are the examples of parameters that contribute to quality of indoor air. Therefore, a study has been carried out by distribute a questionnaire to the students who use badminton court facility in Universiti Tun Hussein Onn Malaysia (UTHM). The purpose of this study is to identify the awareness level and user’s satisfaction towards Indoor Air Quality (IAQ). Data analysis was done using Statistical Package for Social Science (SPSS) and expressed in the form of frequency, percentage and mean. Mean ranking analysis is used to achieve objective one where the highest rank was an air quality plays an important role in ensuring the comfort of users when using the badminton court. Moreover, to achieve objective two mean rank analysis also has been done. As a result, the respondents felt discomfort in using the badminton court facility because of the cumulated water that can be found either at the ceiling or on the floor was the highest rank. In order to achieve objective three, Spearman’s correlation analysis has been used to obtain relationship between awareness and satisfaction level towards IAQ. The result shown a positive relationship which is 0.457 based on Spearman rank-order correlation coefficient. It indicates a strong relationship. In conclusion, if the awareness level is high so, the satisfaction level of the user will easily obtain. From the results, badminton court in UTHM can improve level of IAQ by maintaining and upgrading their facility